Differences between rats and mice in the leptin action on the paraventricular nucleus of the hypothalamus: Implications for the regulation of the hypothalamic‐pituitary‐thyroid axis. (24th August 2020) - Campos, Ana M.P.; Teixeira, Pryscila D.S.; Wasinski, Frederick; Klein, Marianne O.; Bittencourt, Jackson C.; Metzger, Martin; Donato, Jose
Abstract: Previous studies indicate that leptin regulates the hypothalamic‐pituitary‐thyroid (HPT) axis via direct and indirect mechanisms. The indirect mechanism involves leptin action in pro‐opiomelanocortin (POMC)‐ and agouti‐related peptide (AgRP)‐expressing neurones. These cells innervate the paraventricular nucleus of the hypothalamus (PVH) where they modulate hypophysiotrophic thyrotrophin‐releasing hormone (TRH)‐producing neurones. The direct mechanism involves the expression of leptin receptor (LepR) in a subpopulation of PVH TRH neurones. However, to our knowledge, the existence of LepR in PVH TRH neurones of mice has not been clearly confirmed. Therefore, we investigated possible species‐specific differences between rats and mice with respect to the mechanisms recruited by leptin to regulate the HPT axis. We observed that an acute leptin injection induced phosphorylated signal transducer and activator of transcription 3 (pSTAT3), a marker of leptin‐responsive cells, in 46.2 ± 8.0% of PVH proTRH immunoreactive neurones in rats. By contrast, an insignificant number of proTRH positive neurones in the mouse PVH co‐expressed leptin‐induced pSTAT3 or LepR. Similarly, central leptin injection increased the percentage of PVH proTRH neurones containing cAMP response element‐binding protein phosphorylation in rats, but not in mice. We investigated the innervation of AgRP and POMC axons in the PVH and observed that rats exhibited a denser POMC innervation in the PVH compared to mice, whereas rats and mice showed similar density of AgRP axons in the PVH. In conclusion, rats and mice exhibit important species‐specific differences in the direct and indirect mechanisms used by leptin to regulate the HPT axis. Abstract : Previous studies indicate that leptin regulates the hypothalamic‐pituitary‐thyroid axis via direct and indirect mechanisms. In the present study, we demonstrated that the direct action of leptin on thyrotrophin‐releasing hormone (TRH) neurones of mouse paraventricular nucleus of the hypothalamus is not relevant compared to rats that have 46.2 ± 8.0% of TRH neurones exhibiting leptin‐induced phosphorylated signal transducer and activator of transcription 3. Altogether, our findings indicate that rats and mice exhibit important species‐specific differences in the direct and indirect mechanisms used by leptin to regulate the hypothalamic‐pituitary‐thyroid axis.